Domestic Courts and the Interpretation of International Law Methods and Reasoning Based on the Swiss Example - Ammann, Odile (Developments in International Law, 2019)
In Domestic Courts and the Interpretation of International Law, Odile Ammann examines the methodology and reasoning which domestic courts, including Swiss courts, use to interpret international law. She argues that interpretative methods must be taken more seriously in international law. Readership: Domestic judges, academics working on international law, legal theory, and judicial reasoning, academic libraries, advocates, public servants, diplomats, students, and laypersons interested in the relationship between domestic and international law.